Geonarrating Subaltern Stories-so-far - Hawkins, Mike; Palis, Joseph (BANWAAN: The Philippine Journal of Folklore, 2025)
This article narrates and interrogates the spatial politics of Manila’s port area. We ask how land reclamation schemes can be understood as stateled projects that, in part, produce dockside space to secure the uneven relations of capitalist circulation. We draw on interviews with truck drivers conducted during their idle times of waiting outside the entrance gates to the city’s piers. Truckers’ experiences reveal how Metropolitan Manila’s local municipalities, port contractors, and labor unions regulate the daily rhythms and abstract times of port work. We also examine and analyse Jewel Maranan’s documentary Sa Palad ng Dantaong Kulang (2017) as it narrates and gives voice to stories of dispossession among urban poor communities living on reclaimed land on Manila’s waterfront. For most of the men, women, and children Maranan features, global economic and political forces prove to be far more menacing than the shady North Harbor characters looking to make a few pesos. This article concludes by considering how drivers who labor under these circumstances individually and collectively reclaim and leverage control over the concrete times of their daily work. Like the lives of the truck drivers in the port area, Jewel Maranan’s film provides an exceptional portrait of the work necessary to sustain communities and families as the flows of global capitalism continue endlessly beyond the makeshift walls of residents’ homes. Keywords: waterfront, port area, dispossession, reclamation, film